Zombie Norms in Indonesian Regional Law: Measuring Vertical Disharmony with the Job Creation Law Across Three Regulatory Domains - Andi Fatihah Syahrir; Gayatri Putri; Henrietta Noir (Enigma Institute, 2025)
The Job Creation Law (Law No. 11 of 2020, reconstituted as Law No. 6 of 2023) reorganised Indonesian business licensing, spatial-use control, and regional levies, abolishing a generation of sub-national instruments; yet harmonisation of the regional legislative stock has never been measured across domains. Six binary indicators of disharmony — obsolete legal basis, regulation of an abolished instrument, absence of new-regime terminology, pre-reform enactment still in force, a levy attached to an abolished instrument, and no post-2020 amendment or repeal — were aggregated into a 0–6 index. Eighty regional regulations (Perda) from seventy regions, enacted 2001–2025, were coded from official register metadata, each record carrying its verbatim legal-basis citation so that every coding decision is auditable. Seventy-seven instruments (96.3%) remain in force, at a mean index of 4.29 (SD 1.73). Disharmony is a legacy phenomenon: pre-reform instruments scored 5.22 (SD 0.77) against 1.82 (SD 0.91) post-reform (Welch t(33.2) = 15.60, p < 0.001, d = 4.20), an effect surviving controls for domain and tier (b = −3.24; R² = 0.808), while domains did not differ (H = 5.66, p = 0.059). Decisively, absence of post-2020 legislative action alone failed to discriminate between cohorts (Fisher's p = 1.00): regions draft new law correctly but almost never reopen the stock. Five instruments still rest on the colonial Hinder Ordonnantie of 1926. The failure is one of regulatory stock management, traceable to the removal of executive review of Perda in 2017 without substitution, and calls for statutory sunset rules rather than administrative annulment.